Archaeological approaches to the Islamic Emirate of Crete (820s-961 CE): a starting point - Randazzo, Matteo G. (Journal of Greek Archaeology, 2019)
Located at the crossroads between the Western and Eastern Mediterranean, and a gateway to the Aegean and the Greek world, in its millennia of history the island of Crete has been a cultural bridge between Europe, Africa, and Asia. Birthplace of the Minoan civilisation, Homeric land of ‘one hundred cities’, capital of the Roman province of Cyrenaica, and a core region of the Byzantine Empire from the 5th to the early 9th centuries, between the 820s and 961 Crete became an integral component of the Mediterranean Islamic world, and a key ideological and military frontier (taghr) in the Aegean confrontation between Byzantium and the dar al-Islam.